(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The toddler food market in Asian countries has witnessed significant growth due to increasing awareness about nutrition. Key players offer a range of products, including cereals, snacks, and beverages, tailored for toddlers. Factors such as urbanization and changing lifestyles contribute to the expanding market. Local and international brands compete in this segment, focusing on both taste and nutritional value to address the demands of discerning parents. The baby food market, valued at 97.31 billion in 2022, is anticipated to witness growth, projected to increase from 102.90 billion in 2022 to reach 161.16 billion by 2030 (Food Processing and Processed Food, 2022). The present study attempts to identify the reasons of growth in baby food product market in Asian countries. How marketing strategies of companies are leading this market is an interest area of this study.